I respectfully disagree how to have difficult conversations in a divided world - Jones-Fosu, Justin (Berrett-Koehler Publishers, Inc., 2024)
"Start building bridges instead of barriers! This essential guide offers a simple 4-part framework that will help you have honest and enlightening conversations despite deep and fundamental disagreements. Divisions are on the rise around the world, and 2024 may well be a peak year. We're losing the ability to disagree without demonizing. There is a deep need for this practical and accessible guide to having challenging conversations in any situation, from the workplace to the classroom to the dinner table. It's not about saying the right words at the right time but something vastly deeper. In this book, you'll discover the 4 pillars of respectfully disagreeing: Focus on learning not lecturing; Fill in the gaps with curiosity not conclusions; Find the grey, not the black and white; Formulate your plan to humanize and not harm. But this is not a weighty tome. Each chapter features a cartoon, and Justin Jones-Fosu tackles this serious subject with a playful and compassionate tone. For example, he writes "I have become more and more intentional in my desire to respectfully disagree with others (except those who think putting ketchup on eggs is wrong...there is no hope for respect there)." With a wide range of examples and exercises throughout, this is a timely and reader-friendly handbook to disagreeing with someone's ideology while passionately pursuing their humanity"--
Includes bibliographical references and index. - Description based on print version record and CIP data provided by publisher; resource not viewed
Keywords: Interpersonal communication; Interpersonal relations; Communication -- Psychological aspects; Communication interpersonnelle; Communication; Aspect psychologique; Communication; Psychological aspects